ANALISIS YURIDIS PERLINDUNGAN KONSUMEN TERHADAP INFORMASI IKLAN YANG MENYESATKAN - Rizki Tri Anugrah Bhakti, Padrisan Jamba (LPPM Universitas Putera Batam, 2017)
Advertising as one means of marketing and lighting facilities plays animportant role in development. In order for products offered by business actors have high selling value sometimes business actors justifies all means.One of them is through advertising that contains a grandiose promise aboutthe usefulness and benefits of products that suit the needs of consumers. Theneed for regulations that regulate consumer protection because of theweakness of consumer position compared to the position of business actors,because of the process until the production of goods or services that haveproduced consumer intervention at all. Regarding advertising there is nospecific regulatory regulation, but the advertising problem is contained inseveral articles in Law No. 8 of 1999 on Consumer Protection. The mainsource of this research is the data already available in the form of legalprovisions that have been written, which will then be studied according to theprovisions of applicable legislation, as the approach used is normativejuridical is done by reviewing and interpreting things theoretical nature ofprinciples, conceptions, doctrines and legal norms relating to consumerprotection and covenants. Data analysis in this research using qualitativeanalysis. Based on the results of the analysis, deductive conclusions aredrawn, namely the way of thinking based on general facts and then drawn aspecific conclusion.